Ellison Orr letter to Oscar Allert regarding Peregrine Falcon sightings, April 5, 1934 - Orr, Ellisonet al (1934)
Letter from Ellison Orr to Oscar Allert dated April 5, 1934. Orr clarifies his earlier comments on Peregrine Falcon sightings, and mentions some other bird sightings. This letter was summarized in Allert's article "Notes on Certain Raptores in Allamakee, Clayton and Dubuque Counties, Iowa," published in Iowa Bird Life, vol. 9, no. 3. Epson - sheet feed/flatbed